2015
DOI: 10.1080/07391102.2015.1029000
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the cell wall ofMycobacterium tuberculosis: a molecular modeling investigation of the interaction of imipenem and meropenem withL,D-transpeptidase 2

Abstract: The single crystal X-ray structure of the extracellular portion of the L,D-transpeptidase (ex-LdtMt2 - residues 120-408) enzyme was recently reported. It was observed that imipenem and meropenem inhibit activity of this enzyme, responsible for generating L,D-transpeptide linkages in the peptidoglycan layer of Mycobacterium tuberculosis. Imipenem is more active and isothermal titration calorimetry experiments revealed that meropenem is subjected to an entropy penalty upon binding to the enzyme. Herein, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
4
8
0
Order By: Relevance
“…Subsequent to these events, or earlier, precedented retro-aldol reaction can ensue to expel the hydroxyethyl side chain as acetaldehyde 3 , 26 . While these proposals are in agreement with a mechanism of carbapenem-induced inhibition of Ldt Mt2 derived from a theoretical free energy study 27 , our data provide direct evidence of additional cleavage and rearrangement mechanisms beyond the loss of the C6 hydroxymethyl group thought to be common to carbapenems 14 . This information expands design options for carbapenems having alternative modes of transpeptidase inactivation.…”
Section: Discussionsupporting
confidence: 89%
“…Subsequent to these events, or earlier, precedented retro-aldol reaction can ensue to expel the hydroxyethyl side chain as acetaldehyde 3 , 26 . While these proposals are in agreement with a mechanism of carbapenem-induced inhibition of Ldt Mt2 derived from a theoretical free energy study 27 , our data provide direct evidence of additional cleavage and rearrangement mechanisms beyond the loss of the C6 hydroxymethyl group thought to be common to carbapenems 14 . This information expands design options for carbapenems having alternative modes of transpeptidase inactivation.…”
Section: Discussionsupporting
confidence: 89%
“…During geometry optimization it was observed that the carbapenems experienced slight movement inside the binding site of LdtMt2 (Figure 2) as expected 22 . The short-range distances between the sulfur atom of the catalytic cysteine residue and the carbonyl carbon of the βlactam ring of the carbapenem were in the range of 3.6 Å to 3.9 Å.…”
Section: Resultssupporting
confidence: 71%
“…Besides several publications in the field of computer-aided drug discovery for the potential anti-HIV agents made by our research group [19][20][21] , the theoretical binding free energies of the commercially available inhibitors against LdtMt2 were also reported using MM-GBSA and solvation interaction energy (SIE) methods 22 . The role of LdtMt2 flap opening and closing upon complexation of the substrate and three carbapenems, namely: ertapenem, imipenem and meropenem, was also reported using 140 ns molecular dynamics simulation with explicit water solvent 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, SIE (Solvated Interaction Energy) methodology was employed to estimate the binding free energy related to the ligand-receptor complex by applying the boundary element method (BEM) to solve the Poisson-Boltzmann equation. This method also uses implicit solvation in the study of protein-ligand complexes (Naïm et al, 2007;Silva et al, 2016). For this, SIE was used in this study to estimate the binding free energy between BCL-2 and the five phenothiazine derivatives, or the BH3 peptide, from the most stable subtrajectories generated by the MD simulations.…”
Section: Methodsmentioning
confidence: 99%